Atomic resolution view into the structure–function relationships of the human myelin peripheral membrane protein P2. (1st January 2014) - Ruskamo, Salla; Yadav, Ravi P.; Sharma, Satyan; Lehtimäki, Mari; Laulumaa, Saara; Aggarwal, Shweta; Simons, Mikael; Bürck, Jochen; Ulrich, Anne S.; Juffer, André H.; Kursula, Inari; Kursula, Petri
<x xml:space="preserve">Abstract</x> P2 is a fatty acid‐binding protein expressed in vertebrate peripheral nerve myelin, where it may function in bilayer stacking and lipid transport. P2 binds to phospholipid membranes through its positively charged surface and a hydrophobic tip, and accommodates fatty acids inside its barrel structure. The structure of human P2 refined at the ultrahigh resolution of 0.93 Å allows detailed structural analyses, including the full organization of an internal hydrogen‐bonding network. The orientation of the bound fatty‐acid carboxyl group is linked to the protonation states of two coordinating arginine residues. An anion‐binding site in the portal region is suggested to be relevant for membrane interactions and conformational changes. When bound to membrane multilayers, P2 has a preferred orientation and is stabilized, and the repeat distance indicates a single layer of P2 between membranes. Simulations show the formation of a double bilayer in the presence of P2, and in cultured cells wild‐type P2 induces membrane‐domain formation. Here, the most accurate structural and functional view to date on P2, a major component of peripheral nerve myelin, is presented, showing how it can interact with two membranes simultaneously while going through conformational changes at its portal region enabling ligand transfer.